Nanomedicine based on chemotherapy-induced immunogenic death combined with immunotherapy to enhance antitumor immunity - Chen, Yichang; Mao, Kuirong; Han, Dongxiao; Ma, Ruolin; Sun, Tianmeng; Zhang, Haipeng; Han, Bing (Frontiers in Pharmacology, 2024)
Introduction Chemo-immunotherapy based on inducing tumor immunogenic cell death (ICD)with chemotherapy drugs has filled the gaps between traditional chemotherapy and immunotherapy. It is verified that paclitaxel (PTX) can induce breast tumor ICD. From this basis, a kind of nanoparticle that can efficiently deliver different drug components simultaneously is constructed. The purpose of this study is for the sake of exploring the scheme of chemotherapy-induced ICD combined with other immunotherapy to enhance tumor immunogenicity and inhibit the growth, metastasis, and recurrence of breast tumors, so as to provide a research basis for solving the tough problem of breast cancer treatment. Methods Nanomedicine loaded with PTX, small interference RNA that suppresses CD47 expression (CD47siRNA, siCD47), and immunomodulator R848 were prepared by the double emulsification method. The hydrodynamic diameter and zeta potential of NP/PTX/siCD47/R848 were characterized. Established the tumor-bearing mice model of mouse breast cancer cell line (4T1) in situ and observed the effect of intravenous injection of NP/PTX/siCD47/R848 on the growth of 4T1 tumor in situ. Flow cytometry was used to detect the effect of drugs on tumor immune cells. Results NP/PTX/siCD47/R848 nano-drug with tumor therapeutic potential were successfully prepared by double emulsification method, with particle size of 121.5 ± 4.5 nm and surface potential of 36.1 ± 2.5 mV. The calreticulin on the surface of cell membrane and extracellular ATP or HMGB1 of 4T1 cells increased through treatment with NPs. NP/PTX-treated tumor cells could cause activation of BMDCs and BMDMs. After intravenous injection, NP/PTX could quickly reach the tumor site and accumulate for 24 h. The weight and volume of tumor in situ in the breast cancer model mice injected with nanomedicine through the tail vein were significantly lower than those in the PBS group. The ratio of CD8+/CD4+ T cells in the tumor microenvironment and the percentage of dendritic cells in peripheral blood increased significantly in breast cancer model mice injected with nano-drugs through the tail vein. Discussion Briefly, the chemotherapeutic drug paclitaxel can induce breast cancer to induce ICD. The nanomedicine which can deliver PTX, CD47siRNA, and R848 at the same time was prepared by double emulsification. NP/PTX/siCD47/R848 nano-drug can be enriched in the tumor site. The experiment of 4T1 cell tumor-bearing mice shows that the nano-drug can enhance tumor immunogenicity and inhibit breast tumor growth, which provides a new scheme for breast cancer treatment. (Graphical abstract)